Caracterização estrutural do flavonoide C16H14O3 - Mendonça, Nislaine Caetano Silva (2013)
Flavonoids belong to a group of compounds the most important and abundant and occurs in plants, which are widely distributed. And natural compounds are secondary metabolites of plant origin present in many fruits and vegetables and beverages. Are widely studied for their broad spectrum of biological activity, including anti-bacterial, anti-inflammatory, anti-allergic and anticancer To know the structure of these compounds makes it necessary to determine the arrangement of atoms in molecules to understand their chemical, physical and biological. Thus, crystallography is presented as a method of structural determination, by providing a wide application to the elucidation of these molecules and thus presents itself as a fundamental tool for the study of chemical structures with biological activity in the formulation of new drugs. Can be defined by crystallography study of the crystal forms of the proposed structure and symmetry of its forms by X ray diffraction at the atomic level of molecular crystalline materials. This methodology allows the knowledge of the three-dimensional arrangement of atoms in the molecular structure for compounds in the crystalline state. This paper presents fundamental to understanding discussions about the method crystallographic where we have the structure of any chemical compound in a crystalline form.